O processo referencial na libras face às ocorrências anafóricas em língua portuguesa - Reis, Leidiani da Silva (2019)
The process of referencing in languages is produced in interaction, and depends on a series of cognitive, linguistic and discursive factors, being fundamental for the conduction of textual progression, for the constitution of the senses and for the communicative purposes of the interlocutors. This thesis arises, therefore, from the interest of verifying how the referencing behaves in Libras (Brazilian Sign Language). More precisely, the general objective of this research is to analyze the referential processes performed by deaf individuals in Libras in the face of the occurrence of direct anaphora in textual cuts of the Portuguese Language, in a translation bias. Thus, we seek to answer in this research the following questions: (i) How does the anaphora that takes place in the Portuguese Language occurs in the Libras, considering the difference of modality between the two languages? (ii) Does Libras have other categories of reference elements different from those in the Portuguese language? (iii) Is there a difference between the reference strategies mobilized in the Portuguese language and in Libras? In order to reach the proposed objective, and to find answers to the problems listed, we support the research in the theoretical assumptions of Textual Linguistics in which reference is made, among which we can mention the French-Swiss researchers Mondada and Dubois (2003), Apothéloz (2003) ) and Brazilians Koch and Marchuschi (1998), Cavalcante (2000, 2011), Ciulla (2008), Colamarco (2014), Morais (2017), Santos and Cavalcante (2012, 2014); as well as in works related to the referential process in Sign Language, including Pizzuto et al. (2006), Cuxac (2000), Meurant (2008), Schenker (2016, 2013, 2011), Landaluce (2015), Cabeza and García-Miguel (2018), Engberg-Pedersen (2010, 1993), Quadros, Pizzio and Rezende (2009), Ferreira Brito (2010), Bernardino (2000). The research was carried out through a qualitative methodology, through the constitution of a Parallel Corpus Portuguese-Libras, guided by Linguistics of Corpus. As a result of this research process, since Libras is organized spatially, visually, we had few cases similar to those we adopted in the Portuguese language. We observed in the analysis the simultaneous relationship between the anaphora and the dexis present in the glosses-Pounds. Standard-class deictic-anaphoric as well as deictic-anaphoric-class complexes of both manual and non-manual units have been found to be fundamental strategies for conducting the referential chain in Libras.